Macroeconomic Impact On Indonesia's Economic Growth - Nur Zatil Fadilah; Fenty Fauziah; Yulia Tri Kusumawati (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
This study aims to determine the effect of inflation and the rupiah exchange rate on Indonesia's economic growth. This study used a type of quantitative research. The collection of data and information obtained in this study uses secondary data published through the Central Bureau of Statistics, Bank Indonesia, Journal articles and other related research. The data period used is Indonesian data for 2018-2022 in the form of quarters (time series). The data analysis technique used in this study is to use multiple regression models with times series data using Econometric Views Software (Eviews). The results show that inflation partially has a significant effect on economic growth and the exchange rate has no significant effect on economic growth. Simultaneously, inflation and exchange rates have no significant effect on economic growth.